DNA damage and inflammatory response in workers exposed to fuels and paints. Issue 3 (3rd April 2021) - Brum, Evelyne da Silva; da Silva, Lílian Marquezini; Teixeira, Taiane Piccini; Moreira, Laís da Rosa; Kober, Helena; Lavall, Marinês Calegari; Silva, José Édson Paz da; Piana, Mariana; Lenz, Luana Suéling; da Cruz, Ivana Beatrice Mânica; Duarte, Thiago; Duarte, Marta Maria Medeiros Frescura; et al.
Abstract: Workers exposed to fuels and paints may present alterations in several parameters. Thus, we assessed potential biomarkers, with the aim of detecting early changes in gasoline station attendants and painters. Blood samples were collected for the analysis of inflammatory and DNA damage markers, besides biochemical, haematological and oxidative stress parameters. Biochemical and haematological parameters, which are assessed with routine exams, showed few changes. However, these findings could mask the workers' real health status. Besides, markers of oxidative damage were not modified. Levels of inflammatory parameters (cytokines and nitric oxide levels) and the DNA damage marker 8-hydroxydeoxyguanosine were significantly changed in the workers. Our results suggest that inflammatory and DNA damage parameters can be potential biomarkers for the biological monitoring of workers exposed to fuels and paints and may contribute to the development of occupational protection standards.